2005
DOI: 10.1111/j.1365-2958.2005.04882.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐dependent regulation of photosynthesis genes in Rhodobacter sphaeroides 2.4.1 is coordinately controlled by photosynthetic electron transport via the PrrBA two‐component system and the photoreceptor AppA

Abstract: SummaryFormation of the photosynthetic apparatus in Rhodobacter is regulated by oxygen tension and light intensity. Here we show that in anaerobically grown Rhodobacter cells a light-dependent increase in expression of the puc and puf operons encoding structural proteins of the photosynthetic complexes requires an active photosynthetic electron transport. The redox-sensitive CrtJ/PpsR repressor of photosynthesis genes, which was suggested to mediate electron transport-dependent signals, is not involved in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 82 publications
(133 reference statements)
2
39
0
Order By: Relevance
“…Most likely, energy transfer from excited bacteriochlorophyll to oxygen is enhanced when no photosynthetic electron transport can be initiated in the RC. Furthermore, we conclude that photosynthetic electron transport is not involved in light dependent regulation of phrA expression, as demonstrated for the upregulation of photosynthesis genes (Happ et al, 2005).…”
Section: Upregulation Of Phra Expression Depends On Light Intensity Amentioning
confidence: 92%
“…Most likely, energy transfer from excited bacteriochlorophyll to oxygen is enhanced when no photosynthetic electron transport can be initiated in the RC. Furthermore, we conclude that photosynthetic electron transport is not involved in light dependent regulation of phrA expression, as demonstrated for the upregulation of photosynthesis genes (Happ et al, 2005).…”
Section: Upregulation Of Phra Expression Depends On Light Intensity Amentioning
confidence: 92%
“…The regulation by light is initiated by the photosynthetic reaction center and transmitted by the electron transport chain and the PrrBA TCS. In addition, there is a blue-light photoreceptor, AppA, which interferes with the PrrBA-dependent regulation (95). Finally, it has been suggested that RegB in R. capsulatus may respond to additional stimuli, such as the flow of intermediates through the bacteriochlorophyll biosynthetic pathway (1).…”
Section: Regb/prrb-like Redox-responding Global Sensor Kinases With Smentioning
confidence: 99%
“…However, at intermediate oxygen tension blue light, even at low intensities, prevents AppA from binding to PpsR and photosynthesis genes are repressed (8,9), reducing the accumulation of the harmful singlet oxygen. The PrrB/PrrA two-component system senses the electron transport through the cbb3 oxidase and induces transcription of photosynthesis genes at very low oxygen tension or in the absence of oxygen (5,(10)(11)(12)(13). Furthermore, the FnrL protein activates some photosynthesis genes at low oxygen tension (13) and the PpaA regulator activates some photosynthesis genes under aerobic conditions (14).…”
mentioning
confidence: 99%